Identification of the malonylation modification in Staphylococcus aureus and insight into the regulators in biofilm formation - Yu, Xiaoyan; Li, Yi; Yang, Tingting; Li, Wenjie; Dong, Xiaozhu; Huang, Aixiang; Shi, Yanan (Frontiers in Microbiology, 2025)
BackgroundPost-translational modifications (PTMs) are critical regulators of bacterial biofilm formation, but the role of lysine malonylation (Kmal) in biofilm formation is still poorly understood.MethodsIn this study, we analyzed the dynamic changes of protein malonylation of Staphylococcus aureus (S. aureus) DC15 during biofilm formation based on antibody affinity enrichment combined with quantitative proteomics.ResultsQuantitative profiling identified 2,833 malonylated sites across 788 proteins, with significant enrichment in biofilm-associated proteins. Twelve conserved motifs, including Kmal******R and Kmal****R (* represents any amino acid residue), dominated the malonyl proteome landscape in S. aureus. The combined analysis of modified and quantitative proteomics revealed the quorum-sensing system as a key regulatory hub in S. aureus biofilm formation. In particular, the response regulator, AgrA, showed decreased expression but increased malonylation at the K2, K11, and K216 sites during S. aureus biofilm formation, suggesting functional compensation. Structural and phylogenetic analysis showed that the key malonylation sites (K216) of protein AgrA were evolutionarily conserved in Gram-positive pathogens including Bacillus cereus. Molecular docking analysis found that antimicrobial peptide BCp12 and natural compound chlorogenic acid could bind with the malonylation sites in AgrA (ΔG = −6.888 and −5.302 kcal/mol, respectively).ConclusionThis study provides a new perspective for understanding the general rules of bacterial biofilm formation and developing broad-spectrum anti-biofilm drugs.